2017
DOI: 10.1002/pola.28674
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the particle size of the MgCl2 support on the performance of Ziegler catalysts in the polymerization of ethylene to ultra‐high molecular weight polyethylene and the resulting polymer properties

Abstract: A highly systematic size series of Ziegler catalysts with similar porosities and surface textures are synthesized by varying the stirring speed during the MgCl 2 support synthesis. Besides the mean particle size, the only substantial difference observed between the various catalysts is the size and number of nodules per particle. Varying the mean diameter of the catalyst particles between 1.5 and 11.9 mm, leads to a pronounced impact on the activity in ultra-high molecular weight polyethylene (UHMWPE) polymeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
(15 reference statements)
1
24
0
Order By: Relevance
“…are presented in Supporting Information. For the monomodal samples, a correlation between M w and the first melting temperature (MT) is observed (Figure ), which is similar to previous reported data using Ziegler catalysts on these supports . The bimodal PE reactor blend particles do not follow this M w correlation.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…are presented in Supporting Information. For the monomodal samples, a correlation between M w and the first melting temperature (MT) is observed (Figure ), which is similar to previous reported data using Ziegler catalysts on these supports . The bimodal PE reactor blend particles do not follow this M w correlation.…”
Section: Resultssupporting
confidence: 88%
“…In addition, it has previously been demonstrated that highly active postmetallocene catalysts, including the titanium phosphinimide family, can be obtained on MgCl 2 supports . The MgCl 2 support that was employed was based on previously published UHMWPE Ziegler catalyst preparation, where catalyst particle size could be varied from 1.5 to 12 µm …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations